Diversity of Plankton in the Part of Downstrem Siak River, Tualang Village, Tualang Sub-Regency, Siak Regency, Riau Province - Ani Mulyani; Yuliati '; Efawani ' (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2014)
A study on the diversity of plankton in the part of downstrem Siak River wasconducted from May to Juli 2013. This research aims to understand the abundanceand diversity of phytoplankton in that area. There were three stations with 3 samplingpoints in each station. Samples were taken 3 times, once a week and they wereanalyzed in the Aquatic Ecology Laboratory of the Fisheries and Marine ScienceFaculty, Riau University.Result shown that plankton obtained were of 23 genus species, they werebelonged to of 3 classes, namely Bacillariophyceae (6 species), Chlorophyceae(9 species), Cyanophyceae (8 species). The average of phytoplankton abundance wasaround 1083 – 1911 cells/l. The most common phytoplankton was Diatoma sp.(316 cells/l, Bacillariophyceae). Diversity index (H') was 2,88 – 2,99, equitabilityindex (E) was 0,08 – 0,92 and dominancy index (C) was 0,04 – 0,77 and result shownthat the zooplankton obtained consist of 10 genus, they are belonged to 3 classes,namely Rotifera (5 jenis) Ciliata (3 genus), Copepoda (2 genus). The average ofzooplankton abundance was around 409 – 497 ind./l. The most common zooplanktonwas Notholca sp. (123 inds/l, Rotifera). Diversity index (H') was 2,11 - 2,24,equitability index (E) was 0,91 – 0,94 and dominancy index (C) was 0,08 – 0,12.General water quality parameters are as follow: temperature: 29 – 31 0C, pH: 6,transparancy: 29 cm, DO: 3,25 – 4,63 mg/l, CO2: 9,01 – 10,11 mg/l, nitrate:0,09 – 0,12 mg/l, and phosphate 0,013 – 0,016 mg/l.Keywords : Plankton Abundance, Phytoplankton, Zooplankton, Downstrem Siak River